1992
DOI: 10.2172/10184799
|View full text |Cite
|
Sign up to set email alerts
|

Neutron emission from TFTR supershots

Abstract: Empirical scaling relations are deduced describing the neutron emission from TFTR• supershots using a data base that includes all of the supershot plasmas (525) from the 1990 campaign. A physics-based scaling for the neutron emission is derived from the dependence of the central plasma parameters on machine settings and the energy confinement time. Thi:.scaling has been used to project the fusion rate for equivalent DT plasmas in TFTR, aad to explore machine operation space which optimizes the fusion rate. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…8 is plotted the measured neutron rate versus n D P N BI τ s,e with n D the deuterium density (deduced from the electron density and Z ef f measurement), and τ s,e the electron slowing-down time. The beam-target reaction rate computed with the pencil code [31] using the measured kinetic profiles is found to scale linearly with this quantity, as it should [32], and to agree well with the experimental measurement for low to medium NBI power. It is observed that at high NBI power, there is a significant departure of the measured neutron rate from that calculated using pencil, which results from thermonuclear and beam-beam contributions to the neutron rate, although the latter is found not to exceed 10% in these pulses.…”
Section: Neutron Rate and Performancesupporting
confidence: 70%
“…8 is plotted the measured neutron rate versus n D P N BI τ s,e with n D the deuterium density (deduced from the electron density and Z ef f measurement), and τ s,e the electron slowing-down time. The beam-target reaction rate computed with the pencil code [31] using the measured kinetic profiles is found to scale linearly with this quantity, as it should [32], and to agree well with the experimental measurement for low to medium NBI power. It is observed that at high NBI power, there is a significant departure of the measured neutron rate from that calculated using pencil, which results from thermonuclear and beam-beam contributions to the neutron rate, although the latter is found not to exceed 10% in these pulses.…”
Section: Neutron Rate and Performancesupporting
confidence: 70%
“…For these cases, the calculated neutron emission and energy content agreed with the measurements. {[,SNAP/T_ = 0.90 :i: 0.i0 and ESNAp/E "-0.99 =t=0.04) [4] indicating that the plasma measurements were all consistent with each other.…”
Section: Steady-state Transport Calculationsmentioning
confidence: 53%
“…The approach taken in this paper has been to examine all of the supershot plasmas that were obtained during the extensive 1990 run campaign [4]. The data are intended to encompass the full range of plasma behavior encountered in 1990 when TFTR was operated in the supershot mode [5].…”
Section: Tftr Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of the supershot confinement time during the entire CY90 run (aBout 7000 pia.smas) ( Fig. 12)indicates that events such as boronization [18]/rod a disruptive discharge cleaning [19] [15] when tritium is introduced into TFTR supershots. The (x) points did not have blooms, the (r_) points did ha.ve bloom,s.…”
Section: Discharge Cleaningmentioning
confidence: 99%